2020
DOI: 10.1371/journal.pone.0242072
|View full text |Cite
|
Sign up to set email alerts
|

Including residual contact information into replica-exchange MD simulations significantly enriches native-like conformations

Abstract: Proteins are complex biomolecules which perform critical tasks in living organisms. Knowledge of a protein’s structure is essential for understanding its physiological function in detail. Despite the incredible progress in experimental techniques, protein structure determination is still expensive, time-consuming, and arduous. That is why computer simulations are often used to complement or interpret experimental data. Here, we explore how in silico protein structure determination based on replica-exchange mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…pyrexMD was initially developed in the course of (Voronin et al, 2020). Currently, it is successfully applied in ongoing REX studies on protein and RNA structure refinement.…”
Section: Example Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…pyrexMD was initially developed in the course of (Voronin et al, 2020). Currently, it is successfully applied in ongoing REX studies on protein and RNA structure refinement.…”
Section: Example Applicationsmentioning
confidence: 99%
“…Currently, it is successfully applied in ongoing REX studies on protein and RNA structure refinement. (Voronin et al, 2020), such as a minimal TPR threshold of 75% (red) and a suggested optimal number of contacts between L/2 and L (orange), where L denotes the biomolecular sequence length.…”
Section: Example Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In principle, simulations at different temperatures can be used to improve sampling using replica exchange (RE), and the combination of temperature RE with free energy methods can provide computational efficiency. The number of replicas required to span a given temperature difference goes as √ f , where f is the number of degrees of freedom . This scaling means that for protein systems, temperature gaps between replicas can only be 1–3 K, so at least 10 replicas will be required to span a temperature range wide enough (20–30 K) to determine the entropy change. Modified RE methods have, to date, been used successfully in free energy calculations. Those methods scale better with system size by modifying the energy function so that sampling is enhanced along a limited subset of coordinates. , The modified replicas help generate data for low temperatures but do not generate data for higher temperatures.…”
Section: Introductionmentioning
confidence: 99%